DAIRY GOATS, NUTRITIOUS AND TECHNOLOGICAL VALUE OF GOAT MILK - Мекић, Цвијан; Трифуновић, Григорије; Христов, Славча; Новаковић, Зорица (Economics of Agriculture, 2018)
Goat milk is valuable biological food designed for kid nourishment as well as industrial raw material for making different milk products. Goats differentiate from other species of domestic animals by their specifc biological and zoo-technical traits. Compared to their own body weight goats give ten times more milk, yearly they produce two kids, also for one unit of product they utilize much less nutrients than cows and sheep, moreover they have very high coeffcient for utilization of nutrients from bulky feed Goat milk has nutritious and health advantages compared to cow milk, it is much easier for digestion and it has antiallergenic nature. To improve dairy goat structure by importing the noble races of goats we should choose Alpino, Sanska and German multicolored breed. With application of selection work and improvement of breeding conditions for goat milk production we can also use specially selected breeding stock of domestic white goat.